Seeing atomic-scale structural origins and foreseeing new pathways to improved thermoelectric materials. Issue 8 (17th June 2019) - Wu, Haijun; Zhang, Yang; Ning, Shoucong; Zhao, Li-Dong; Pennycook, Stephen J.
Abstract : Thermoelectricity enables the direct inter-conversion between electrical energy and thermal energy, promising for scavenging electric power from sources of waste heat and protecting solid-state refridgerating electronic devices from overheating. Abstract : Thermoelectricity enables the direct inter-conversion between electrical energy and thermal energy, promising for scavenging electric power from sources of waste heat and protecting solid-state refridgerating electronic devices from overheating. The low energy conversion efficiency limits such smart materials from being put into widespread use. Despite persistent efforts to optimize the overall thermoelectric performance via band engineering and nanostructuring, information on atomic-scale defects and their effects on transport properties remains lacking. With the development of aberration-corrected scanning transmission electron microscopy (STEM), directly seeing and tuning all scales of defects has now become possible, including the critically important atomic-scale defects. Thoroughly understanding the nature and role of structural defects not only reveals the origin of the structure–property correlations of existing high-performance materials, but more significantly, enables us to foresee new pathways for the exploration of new materials with enhanced properties. Here we demonstrate several examples of new insights obtained from classical and new-generation thermoelectric materials. Finally, we propose to unravel the static lattice distortion and dynamic lattice vibrations of atomic-scale defects through ex situ and in situ aberration-corrected STEM. We highlight a brand-new, universal strategy, atomic-scale defect engineering, to optimize the properties of functional energy materials, which goes beyond the widely acknowledged nanostructuring.